THE STATE OF FOOD SECURITY IN THE WORLD AND UZBEKISTAN (Web of Teachers: Inderscience Research, 2024)
This article explores the current state of food security both globally and within Uzbekistan. It delves into the factors influencing food access, availability, and stability while also considering the implications of climate change, economic fluctuations, and policy initiatives. The analysis highlights Uzbekistan's unique challenges and achievements within the broader context of international food security trends.